Paths of Spiritual Devotion: Investigating Urip Sejati Adherents in Onggosoro, Giritengah, through the Lens of Religious Moderation - Siti Robikah; Muhammad K. Ridwan (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2023)
This research delves into the phenomenon of Urip Sejati adherence among the community of Onggosoro in Giritengah. Urip Sejati is a religious concept rooted in Javanese spirituality, emphasizing a path of devotion that seeks inner enlightenment and harmony. The study employs a comprehensive lens of religious moderation to examine individuals' practices, beliefs, and attitudes to illuminate how Urip Sejati followers negotiate their spiritual pursuits within the context of contemporary religious dynamics. Drawing upon a qualitative approach, data was collected through in-depth interviews, participant observation, and analysis of relevant documents. The research sought to explore the extent to which Urip Sejati adherents embody religious moderation in their daily lives, how their practices reflect principles of inclusivity, tolerance, and interfaith dialogue, and whether their spiritual journey promotes social cohesion within the broader community. Findings reveal diverse expressions of Urip Sejati devotion, with adherents navigating a balance between individual spiritual exploration and communal interconnectedness. Furthermore, the study uncovers various factors influencing religious moderation within the Urip Sejati context, including historical and cultural backgrounds, socio-political dynamics, and interactions with neighboring religious traditions. This research contributes to the existing discourse on religious moderation, highlighting the significance of local spiritual practices in fostering tolerance and coexistence. It underscores the need for nuanced understandings of religiosity beyond traditional institutional frameworks and posits Urip Sejati as a compelling case study for engaging with the intricacies of religious diversity in contemporary society. The findings not only enrich our comprehension of Urip Sejati as a religious phenomenon but also contribute to broader discussions on the dynamic interplay between devotion, moderation, and communal dynamics in the realm of faith